2021
DOI: 10.31153/ppis.2020.89
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Standar Lantanum Terhadap Validasi Metode Pengukuran Neodimium dan Serium Menggunakan X-Ray Fluorescence (XRF)

Abstract: Telah dilakukan analisis unsur Neodimium (Nd) dan Serium (Ce) pada sampel cair menggunakan XRF. Spektrometer. XRF pada umumnya digunakan untuk analisis sampel berbentuk padat. Bila sampel yang dianalisis berbentuk cair maka perlu preparasi khusus agar hasil analisis memenuhi persyaratan pengujian dan memenuhi kriteria keselamatan. Laarutan standar Nd dan Ce sebanyak 50uL diteteskan di kertas saring berdiameter 24mm dengan konsentrasi yang bervariasi 200, 400, 600, 800 dan 1000ppm tanpa pembanding La dan dengan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…In addition, the calibration results showed that the resolution was 162.7 eV. This means that characteristic X-ray spectral peaks were separated perfectly when they have an energy difference greater than 162.7 eV [17]. As confirmed in the obtained spectrum to be analyzed, it is known that the peak of the characteristic Xray energy spectrum of Nd was at 5.25 keV (Lα) and 5.75 keV (Lβ).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, the calibration results showed that the resolution was 162.7 eV. This means that characteristic X-ray spectral peaks were separated perfectly when they have an energy difference greater than 162.7 eV [17]. As confirmed in the obtained spectrum to be analyzed, it is known that the peak of the characteristic Xray energy spectrum of Nd was at 5.25 keV (Lα) and 5.75 keV (Lβ).…”
Section: Resultsmentioning
confidence: 52%
“…The optimum recovery of Cs separation was obtained. The reaction that occurred in the separation of Nd and Cs in a nuclear fuel solution using the precipitation method is as followed [17].…”
Section: Introductionmentioning
confidence: 99%
“…Aplikasi zeolit, baik alami maupun yang dimodifikasi, telah banyak dimanfaatkan di berbagai bidang baik sebagai adsorben [10], katalis [11], pengering [12], penukar ion [13], [14] dan bahan bangunan [15]. Pemanfaatan zeolit sebagai adsorben banyak digunakan untuk menghilangkan senyawa organik dan logam berat dari limbah industri.…”
Section: Pendahuluanunclassified